(untitled) (Research, Society and Development, 2021)
The operating room is a complex, restricted unit, in which the team is faced with several situations that can be perceived as stressors. The study aimed to describe the scientific evidence found in the scientific literature from 2015 to 2020, about stressors and their consequences, for nursing professionals at work in the operating room. This is an integrative literature review study, descriptive, with a qualitative approach. The databases searched were BVS, LILACS and SciELO. For data extraction, the Ursi & Galvão form was used. For the critical analysis of the studies, the classification system by hierarchy of evidence was applied. The study sample consisted of nine original articles. The results were presented and discussed from two thematic categories: Stress factors at work in the operating room and the consequences of stress at work in the operating room. Divided and submitted to a variety of positions that generate wear and tear. Nursing was considered to be a stressful profession and this is related to working with people who suffer and require a great deal of attention. It was concluded that the occupational stress factors are of an environmental, social, professional nature, mainly related to the nature of the activities developed, the number of professionals, the planning of activities, materials and equipment, interpersonal relationships, are factors that have physical and psychological consequences.